New insights into the first cervical vertebrae of Otavipithecus and Nacholapithecus - Amélie Beaudet; Yasuhiro Kikuchi; Fredrick Kyalo Manthi; Emmanuel Ndiema; Dominic Stratford; Bernhard Zipfel (Scientific Reports)
Abstract Fossil hominoids are crucial to understand the selection pressures that played a role in the emergence of modern hominoid positional behaviors. Here we investigate the morphology of the atlas of Otavipithecus namibiensis (GSN BA 104’91, Namibia) and Nacholapithecus kerioi (KNM-BG 35250BE, Kenya) for identifying potential positional-related signals and discussing functional and evolutionary implications. Published data from GSN BA 13’21, a second Otavipithecus atlas from Namibia, were integrated. For comparative material, 105 atlases of extant catarrhines and platyrrhines were included. In addition to standard linear measurements, the morphology of GSN BA 104’91 and KNM-BG 35250BE was investigated by landmark-based geometric morphometric (GM) method and statistical analyses. The dimensions of the Miocene specimens fall within, or closely approximate to, the range of variation of Pan and Hylobates. Our GM analyses indicate that GSN BA 104’91 is more similar to Pan. When the right lateral mass only is considered, GSN BA 104’91 and KNM-BG 35250BE show similarities with hominoids and cercopithecoids. Our results possibly support a positional repertoire in Otavipithecus that would have been partly similar with extant hominoids, and in particular with Pan (e.g., terrestrial quadrupedalism, climbing), and the presence of a mix of hominoid-like and cercopithecoid-like traits in the axial skeleton of Nacholapithecus.